Human Versus Artificial Intelligence in Creative Physics Thinking: A Philosophical Reflection on Learning and Cognition - Sofita, Mita; Damarsha, Adrian Bagas; Prasetya, Joenathan Eka; Yuliatin, Elisa Dwi; Rahma, Nur Fitri; Jauhariyah, Mukhayyarotin Niswati Rodliyatul; Saphira, Hanandita Veda (Studies in Philosophy of Science and Education, 2024)
The rapid advancement of artificial intelligence (AI) has led to its increasing integration into education, including in subjects like physics that require high-level cognitive skills. This study compares human responses with those generated by AI models (ChatGPT and DeepSeek) to physics problems designed to measure creative thinking skills while exploring the philosophical patterns in AI reasoning as a reflection of human cognition. Using a qualitative-comparative method, responses were analyzed based on fluency, elaboration, originality, and flexibility, focusing on the concept of moment of inertia within the traditional "Kekehan" game. Findings show that while AI responses demonstrated structured reasoning and elaboration, human answers were more contextually relevant and original, rooted in experience. DeepSeek produced more detailed responses than ChatGPT, but both showed tendencies toward generalization. The results indicate that AI, though useful as a support tool, lacks the genuine creativity of human thinking. The study suggests that reliance on AI in education should be balanced with strategies that foster human creativity and critical thinking. Philosophical reflection is necessary to redefine AI's role in education, ensuring it complements rather than replaces human intellectual development.